(untitled) (Revista de Ciências Agroveterinárias, 2014)
This work was carried out to evaluate the effects of mechanical damages on quality and ripening of ‘Laetitia’ plums stored at ambient temperature (23°C±5ºC and 65±5% RH). The treatments evaluated were control (no mechanical damage), mechanical damage by impact (drop from 10 and 15 cm) and mechanical damage by compression of 25 N (on two and four sides of the fruit). Fruits were evaluated for respiration rate at 0, 12, 24, 48, 72, and 120 h after being damaged. After three and five days fruit were assessed in terms of flesh firmness, texture (forces for flesh penetration and fruit compression), titratable acidity, soluble solids content, and color (lightness and ‘hue’ angle) of the skin and flesh (damaged and not damaged). In general, the mechanical damages tested by impact and compression did not affect quality and ripening of ‘Laetitia’ plums at the ambient condition.